Resource prediction-based routing using agents in mobile ad hoc networks. (2018) - Chaudhari, Shilpa Shashikant; Biradar, Rajashekhar C.
QoS outing in multimedia applications over MANET is affected by limited resources, shared channel, unpredictable mobility, improper load balancing, and variation in signal strength. Existing works on MANET QoS routing focuses on only one of the factor such as bandwidth, mobility or energy neglecting dependent behaviour. In this paper, resource prediction-based routing is proposed wherein intelligent agents identify routes for communication with adequate future availability of buffer-space, energy and bandwidth resources considering mobile nodes. It has four steps of execution: resource prediction, resource prediction factor computation, route establishment, and route maintenance. Resources are predicted to compute resource prediction factors for reliable route establishment and route maintenance against link and node failure. Simulation results show an improvement in terms of packet delivery ratio, packet delivery latency, memory overhead and energy consumption.